THE INFLUENCE OF MANAGERIAL ABILITY TOWARDS ACCOUNTING CONSERVATISM (A Study in Non-Cyclical Companies Listed on IDX) - Handoko, Maria Evelyn Jenita; Fuad, Fuad (JURNAL AKUNTANSI DAN AUDITING, 2023)
The purpose of this study is to examine whether managerial ability affects positively to conditional and unconditional conservatism among non-cyclical companies listed on Indonesia Stock Exchange (IDX). The data used in this study uses secondary data taken from the company’s annual report that is provided in Indonesian Stock Exchange website as well as Bloomberg’s Financial Analysis (FA) and Equity Screening (EQS) for the period 2012 to 2022. In this study, the population are non- cyclical or consumer goods companies listed on the Indonesia Stock Exchange (IDX) and the sampling method used is purposive sampling technique. In the process of analysis, this research uses multiple linear regression with robust standard error method. The results of the analysis show that managerial ability affects in mixed way such as positive, negative and some even have no effect either to conditional conservatism. In addition, it affects positively to unconditional conservatism. To the best of the authors’ knowledge, few studies have explored the influence of managerial ability on accounting conservatism. For non-cyclical firms, this study’s result gives significant contribution which focuses on examining the association between managerial ability and accounting conservatism, which has not been widely used in local studies.